1996
DOI: 10.1002/(sici)1097-4652(199607)168:1<114::aid-jcp14>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of BCL-2 with membrane hyperpolarization and radioresistance

Abstract: The resting membrane potential of parental, neomycin control, and Bcl-2 transfected cells was measured, and the effect of membrane hyperpolarization or depolarization on radiosensitivity was studied. Bcl-2 transfected cells were significantly more radioresistant than control cells and were significantly hyperpolarized compared to parental and neomycin control transfected PW and HL60 cells. Hyperpolarization of the parental and neomycin control transfected cells by valinomycin significantly increased the radior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…A variety of biophysical mechanisms for transducing membrane voltage changes to secondary messenger effectors are now known (Cherubini et al, 2005;Levin et al, 2006;Murata et al, 2005). Our data suggest that control of regeneration by V-ATPase-dependent proton flux may take place through at least two mechanisms: control of cell number through modulation of membrane voltage (Cone, 1974;Cone and Cone, 1976;Gilbert et al, 1996;Olivotto et al, 1996;Tseng et al, 2007), and proper guidance of axon growth into the regenerate.…”
Section: Research Articlementioning
confidence: 77%
“…A variety of biophysical mechanisms for transducing membrane voltage changes to secondary messenger effectors are now known (Cherubini et al, 2005;Levin et al, 2006;Murata et al, 2005). Our data suggest that control of regeneration by V-ATPase-dependent proton flux may take place through at least two mechanisms: control of cell number through modulation of membrane voltage (Cone, 1974;Cone and Cone, 1976;Gilbert et al, 1996;Olivotto et al, 1996;Tseng et al, 2007), and proper guidance of axon growth into the regenerate.…”
Section: Research Articlementioning
confidence: 77%
“…Accordingly, long-term clonogenic assays also demonstrated that only Bcl-x L provided protection for DU-145 cells (Figure 6, panel c). Multiple reports confirm that prevention from apoptosis by Bcl-2 following DNA damage does not guarantee enhanced long-term tumor cell survival (Sentman et al, 1991;Collins et al, 1992;Strasser et al, 1994;Gilbert et al, 1996;Lock and Stribinskiene, 1996;Kyprianou et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, up-regulation of the antiapoptotic Bcl-2 family members in certain tumors has been implicated in their chemo-and radioresistance. 10,11 Chondrosarcoma and other sarcomas are known to express genes that regulate both cell death and cell survival. 12 Therefore, down-regulating antiapoptotic genes may be one logical approach in enhancing the efficacy of radiation and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%